Evaluasi dan Perancangan Desain Solusi Website Badan Pendapatan Pengelola Keuangan dan Aset Daerah (BPPKAD) Kota Kediri menggunakan Metode Webqual, Design Thinking dan System Usability Scale (SUS) - Rayyan Mada; Satrio Hadi Wijoyo; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Regional Financial and Asset Management Agency of Kediri website is a media for storing information related to profiles, services, registration, reporting or payment of taxes and levies, activities documentation, news to socialization as an effort to implement electronic-based government to improve the quality of public services effectively and efficiently. Although this website is one of the information media for Kediri City BPPKAD, there are still deficiencies found, especially related to information quality, service interaction quality, website usability and user experience. Referring to the finding of these deficiencies, this research was conducted to evaluate and redesign the website of the Kediri City BPPKAD, in order to improve the usability aspect of the website. Then in the website design process, the design thinking method will be carried out with task scenario testing and also SUS testing too. Based on the initial needs excavation, it was found that the satisfaction level of website users was only around 66%. The lowest level of satisfaction is in the aspect of content, organization and readability. While the highest level of satisfaction is in the user interface design aspect, although it is only around 70%. Then the results of the evaluation and redesign were carried out to obtain satisfactory results. Based on the aspect of effectiveness and efficiency, 100% of users have succeeded in executing the given task scenario with the longest processing time being 10 seconds for one task. Then in the satisfaction aspect, the average user gives an assessment on a grade scale of B+ to A+.